Parental and Social Environment Support: Key Determinants of Learning Motivation and Achievement in Elementary School Physical Education - Yudaparmita, Gusti Ngurah Arya; Nirmayani, L. Heny (Universitas Pendidikan Ganesha, 2024)
The low motivation and academic performance of students in Physical Education, Sports, and Health (PJOK) at the elementary school level remain common issues, primarily due to a lack of support from families and social environments. This study aims to analyze the role of parental and social environment support in influencing students' learning motivation and academic achievement in PJOK. The research employed a correlational design, involving 161 elementary school students as samples, selected randomly using the simple random sampling technique. Data collection instruments included questionnaires to measure parental support, social environment, and learning motivation variables, as well as PJOK academic achievement data obtained from school documents. Data were analyzed using path analysis to identify causal relationships between variables. The results revealed a significant positive relationship between parental support, social environment, and students' learning motivation. Additionally, learning motivation significantly influenced students' academic performance. Parental support and the social environment indirectly affected academic performance through learning motivation. These findings indicate that collaboration between families and the social environment is crucial in shaping students' motivation and academic success. This study implies that strengthening the role of parents and the social environment can enhance students' motivation and academic achievement in PJOK.